Online oral hygiene instructions for orthodontic patients in Malaysian population - Malini A,; Asma AAA,; Nurul Asyikin Yahya, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Fixed orthodontic appliances causes plaque accumulation, which leads to the formation of dental caries and gingivitis. Therefore, concise oral hygiene instructions (OHI) is necessary to avoid the occurrence of these diseases. Massive Open Online Course (MOOC) ensures interactive learning to improve knowledge retention. MOOC transfers the responsibility of learning OHI to the patients with remote guidance from the clinician, thus reduces clinical time. This research aimed to develop the MOOC learning content on OHI in orthodontic practice. The secondary aim was to assess the overall analytics data among learners enrolled for the completion rate and time taken to complete the MOOC. The ADDIE principles which were, "Analyse, Design, Develop, Implement and Evaluate", were used to develop the MOOC. The contents were based on a published pamphlet of OHI from the Ministry of Health, Malaysia. The MOOC was pre-tested, and content was improved based on the feedback from users and experts. The MOOC named “Penjagaan Kebersihan Pendakap Gigi” utilises the Bahasa Melayu language to educate learners regarding oral care with orthodontic appliances. Sixty-two learners joined the MOOC, with 77.4% achieving a high rate of completion of the MOOC learning content. There were forty-six female learners (74.2%), while male learners comprised sixteen (25.8%). The median (interquartile range) time taken to complete MOOC learning content were 31.50 minutes, (13.00 minutes to 55.50 minutes). This shows that MOOC could be an alternative platform to instruct patients on OHI with fixed appliances. MOOC can potentially reduce clinical time to teach OHI to patients.